Late antique motifs in Yezidi oral tradition - Spät, Eszter (Gorgias dissertations, 2010)
Religious movements in the Middle East -- The origin of the Yezidis and of Yezidi studies -- The religion of the Yezidis -- Religious oral tradition and literacy among the Yezidis of Iraq -- The Yezidi creation myth of Adam -- The khirqe, or garment of faith -- "The song of the commoner" : the motif of sleep and awakening -- The origin myth of the Yezidis : the myth of Shehid Bin Jer -- The birth of Prophet Ismail in the Yezidi "Tale of Ibrahim" -- Epilogue : late antique motifs and modern Yezidism -- Appendix I : transcript of recordings of the myth of Adam and the myth of Shehid Bin Jer -- Appendix II : Yezidi hymns translated by P. Kreyenbroek